2003
DOI: 10.1097/00002060-200301000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Postural Control During Sit-to Stand and Gait in Stroke Patients

Abstract: Hemiplegic stroke patients, who could stand up within 4.5 sec or who had a maximal vertical force difference of less than 30% of body weight between both legs, had better gait performance than the others did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 14 publications
4
85
1
Order By: Relevance
“…Three studies using the positioning foot strategies, found shorter time in the performance of standing up from spontaneous position when compared to the symmetric and asymmetric in hemiparetic patients. (8,11,13) The duration to complete the task on the spontaneous position of feet on the above studies was shorter (2,6; 2,7 and 1,93 s) than reported by Chou e outros, (5) 2003, in his study about hemiparetic subjects (4,5s).…”
Section: Image 1 -Flowchartmentioning
confidence: 49%
See 2 more Smart Citations
“…Three studies using the positioning foot strategies, found shorter time in the performance of standing up from spontaneous position when compared to the symmetric and asymmetric in hemiparetic patients. (8,11,13) The duration to complete the task on the spontaneous position of feet on the above studies was shorter (2,6; 2,7 and 1,93 s) than reported by Chou e outros, (5) 2003, in his study about hemiparetic subjects (4,5s).…”
Section: Image 1 -Flowchartmentioning
confidence: 49%
“…(8,12) After stroke automatic program to get up may be compromised by muscle weakness in the paretic side. (5) Study investigated the relationship of muscle strength with the transfer from sitting to standing identified the association of paretic knee extensors and ankle extensors with the performance of standing up in subjects after stroke.…”
Section: Image 1 -Flowchartmentioning
confidence: 99%
See 1 more Smart Citation
“…When stroke patients perform STW, they experience difficulties in the STS movements that need to be made before the initiation of walking, because they cannot produce the joint extension momentum and force for standing from the sitting position due to muscle weakness and postural control impairment [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The ability to effectively perform the sit-to-stand and stand-to-sit activities (3)(4)(5) are important pre-and post-requisites for upright mobility (5,6) and, therefore, for the performance of other common daily activities. Thus, these functional activities are fundamental components for the independence of persons with disabilities (2,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%